Analisis Pendapatan Petani serta Faktor yang Mempengaruhi Produksi Padi Sawah di Kecamatan Baktiya Kabupaten Aceh Utara - Rahmat Suryanto Pirngadi; Jana Putri Utami; Aflahun Fadhly Siregar; Salsabila Salsabila; Wildani Lubis; Dian Retno Intan (JURNAL AGRICA, 2023)
Aceh Utara is the largest rice producing district in Aceh Province in the last five years with a total production of 393,477 thousand tons in 2020. The high production of lowland rice in Aceh Utara District cannot be separated from the high production of lowland rice in Baktiya Sub-District with total production reaching 50,347 thousand tons with an average productivity of 5.4 tons/ha in 2020. The purpose of this study is to analyze the income of lowland rice farming, as well as to see what factors affect the production of lowland rice farming in Baktiya Sub-District in the Aceh Utara District. The method of determining the sample using random sampling method with the number of respondents as many as 140 rice farmers, while the data analysis method uses the Cobb-Douglas function analysis approach. The results of this study found that the net income received by rice farmers in Baktiya Sub-District, Aceh Utara District within one year was Rp.39,526,000/Ha/year. The description of the model to see the factors that affect the production of lowland rice in the Baktiya Sub-District, it is found that all independent variables have a positive effect on the factors that affect the production of lowland rice farming. In the partial test, the variables of land area and fertilizer have a significant effect on the factors that affect the production of lowland rice in the Baktiya Sub-District.